Pemodelan Strategi Komunikasi Pemasaran Lokananta - Surya Ageng Priambudi; Mahfud Anshori (Universitas Sebelas Maret (UNS), 2024)
This modern era currently demands various companies for having marketing activities inside of it, which are expected to build the company's image, improving the performance and existence of the company, also creating good relationships with its audience. However, in order to realize these marketing activities, communication planning are crucial for compiling a marketing communication strategy model as a guideline for carrying out the company's marketing activities. Lokananta is known as the oldest recording studio and the only legendary factory which produces vinyl records that has ever built in Indonesia. Since there was a construction that happened in this company, many changes have occurred, including its marketing communication that carries out. The researcher here found out that Lokananta has carried out several of its marketing activities, but does not yet have an official document that shows the marketing communication planning guideline that it carries out to gain widespread public attention. This research aims to design and form a marketing communication strategy model that is used as a guide by Lokananta’s management in carrying out its marketing activities sustainably. The method in this study uses a qualitative approach, with data collection techniques in the form of interviews and document studies. The results that has obtained from this study are the creation of a marketing communication strategy model involving the use of the SOSTAC model (Situation, Objective, Strategy, Tactic, and Control) and a marketing communication mix from the Integrated Marketing Communication (IMC) concept which is used as a strategic guide in sustainable marketing efforts that make it easier for the management of Lokananta.